The role of cumulative physical work load in lumbar spine disease: risk factors for lumbar osteochondrosis and spondylosis associated with chronic complaints. Issue 11 (1st November 2001) - Seidler, A; Bolm-Audorff, U; Heiskel, H; Henkel, N; Roth-Küver, B; Kaiser, U; Bickeböller, R; Willingstorfer, W J; Beck, W; Elsner, G
Abstract : OBJECTIVES: To investigate the relation with a case-control study between symptomatic osteochondrosis or spondylosis of the lumbar spine and cumulative occupational exposure to lifting or carrying and to working postures with extreme forward bending. METHODS: From two practices and four clinics were recruited 229 male patients with radiographically confirmed osteochondrosis or spondylosis of the lumbar spine associated with chronic complaints. Of these 135 had additionally had acute lumbar disc herniation. A total of 197 control subjects was recruited: 107 subjects with anamnestic exclusion of lumbar spine disease were drawn as a random population control group and 90 patients admitted to hospital for urolithiasis who had no osteochondrosis or spondylosis of the lumbar spine radiographically were recruited as a hospital based control group. Data were gathered in a structured personal interview and analysed using logistic regression to control for age, region, nationality, and other diseases affecting the lumbar spine. To calculate cumulative forces to the lumbar spine over the entire working life, the Mainz-Dortmund dose model (MDD), which is based on an overproportional weighting of the lumbar disc compression force relative to the respective duration of the lifting process was applied with modifications: any objects weighing ⩾5 kg were included in the calculation and no minimum daily exposure limits were established. Calculation of forces to the lumbar spine was based on self reported estimates of occupational lifting, trunk flexion, and duration. RESULTS: For a lumbar spine dose >9×10 6 Nh (Newton×hours), the risk of having radiographically confirmed osteochondrosis or spondylosis of the lumbar spine as measured by the odds ratio (OR) was 8.5 (95% confidence interval (95% CI) 4.1 to 17.5) compared with subjects with a load of 0 Nh. To avoid differential bias, forces to the lumbar spine were also calculated on the basis of an internal job exposure matrix based on the control subjects' exposure assessments for their respective job groups. Although ORs were lower with this approach, they remained significant. CONCLUSIONS: The calculation of the sum of forces to the lumbar spine is a useful tool for risk assessment for symptomatic osteochondrosis or spondylosis of the lumbar spine. The results suggest that cumulative occupational exposure to lifting or carrying and extreme forward bending increases the risk for developing symptomatic osteochondrosis or spondylosis of the lumbar spine.